Peran Kepemimpinan Islam dalam Mewujudkan Pendidikan Berakhlak Mulia - Sillia Iriana, Sillia Iriana; Hengelina (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study is to provide a more holistic leadership strategy, including the application of the principles of shiddiq, tabligh, fathanah, and syaja'ah in a modern context. The research method used is library research, focusing on key issues related to Islamic educational leadership. Data collection techniques involve identifying discourse from various sources such as books, articles, magazines, and journals related to leadership in Islam. The data is then analyzed using descriptive methods. The results of the study indicate that Islamic educational leadership plays a crucial role in realizing noble character education through the integration of traditional Islamic values such as amanah (trustworthiness), adil (justice), syura (consultation), and amar ma'ruf nahi munkar (enjoining what is good and forbidding what is evil), as well as the principles of shiddiq, tabligh, fathanah, qana'ah, and syaja'ah. Islamic educational leaders are not only responsible for managing educational institutions but must also be able to adapt to digital technology developments, create a conducive learning environment, and guide the younger generation to have noble character. The success of educational institutions heavily depends on dynamic, innovative leadership focused on improving educational quality, grounded in the moral values of the Quran and Hadith. The implications of this research highlight the importance of Islamic education leaders addressing modern challenges such as technological literacy and data management while maintaining the integrity and ethics of Islamic leadership.